Some questions about the old and the new SEO - Codina, Lluís (Anuario ThinkEPI, 2015)
The changes introduced in the Google algorithms in recent years have led to an apparent loss of relevance of SEO (search engine optimization) as a field of study and practice. The characteristics of the old and the new SEO are examined, arriving at the conclusion that SEO remains as relevant as ever, or even more so. As a result of the changes introduced, the new SEO is more oriented in favor of user experience, compared to the old algorithms.